2015
DOI: 10.1007/s13197-015-1963-4
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol extract of mango (Mangifera indica L.) peel inhibits α-amylase and α-glucosidase activities, and ameliorates diabetes related biochemical parameters in streptozotocin (STZ)-induced diabetic rats

Abstract: Peel is a major by-product during processing of mango fruit into pulp. Recent report indicates that the whole peel powder ameliorated diabetes. In the present study, ethanolic extract of mango peel was analysed for its bioactive compounds, evaluated for α-amylase and α-glucosidase inhibitory properties, oral glucose tolerance test, antioxidant properties, plasma insulin level and biochemical parameters related to diabetes. In addition to gallic and protocatechuic acids, the extract also had chlorogenic and fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(58 citation statements)
references
References 75 publications
6
50
0
2
Order By: Relevance
“…Concomitantly, red mango fruit with enhanced anthocyanin and flavonoid contents show improved resistance to fungal pathogens and better cold tolerance (Sivankalyani et al, 2016b;Sudheeran et al, 2018). Previous studies have shown that extracts of M. indica possess a variety of compounds, including proteins, carbohydrates, minerals, phenolic compounds and dietary fiber (Gondi & Rao, 2015), which has antiviral and antibacterial activities (Makare et al, 2001). Previous studies have shown that extracts of M. indica possess a variety of compounds, including proteins, carbohydrates, minerals, phenolic compounds and dietary fiber (Gondi & Rao, 2015), which has antiviral and antibacterial activities (Makare et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Concomitantly, red mango fruit with enhanced anthocyanin and flavonoid contents show improved resistance to fungal pathogens and better cold tolerance (Sivankalyani et al, 2016b;Sudheeran et al, 2018). Previous studies have shown that extracts of M. indica possess a variety of compounds, including proteins, carbohydrates, minerals, phenolic compounds and dietary fiber (Gondi & Rao, 2015), which has antiviral and antibacterial activities (Makare et al, 2001). Previous studies have shown that extracts of M. indica possess a variety of compounds, including proteins, carbohydrates, minerals, phenolic compounds and dietary fiber (Gondi & Rao, 2015), which has antiviral and antibacterial activities (Makare et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Mango peel, leaves, and mango kernel flour have been used to modulate glycemia in animal models, but are not part of South Asian diet. [8][9][10]…”
Section: Usagementioning
confidence: 99%
“…Pulp and leaf extracts of mango produced a significant hypoglycemic effect in streptozotocin (STZ)-induced diabetic rats [25][26][27]. Furthermore, Gondi et al [28] showed that also mango peel extracts have the ability to ameliorate diabetes. In fact, administration of different doses of peel extracts to STZ-induced diabetic rats resulted in significant decline in blood glucose levels, increased plasma insulin level as well as decreased levels of fructosamine and glycated hemoglobin, two diabetes status indicators.…”
Section: Anti-inflammatory Effects Of Mangomentioning
confidence: 99%
“…The anti-diabetic effect of mango peel extracts can be partially attributed to their ability to inhibit α-amylase and α-glucosidase, the carbohydrate hydrolyzing enzymes. This effect may be due to the presence of polyphenolic acids, like gallic acid, chlorogenic acid and ferulic acid, which have been shown to inhibit α-amylase and α-glucosidase activities [28]. Subclinical low-grade inflammation plays an important role in the pathogenesis of insulin resistance.…”
Section: Anti-inflammatory Effects Of Mangomentioning
confidence: 99%